Optical Transmission-Based Water Turbidity Measurement System - Ahmad Shauri, Ruhizan Liza (2006)

(untitled)
Turbidity is one of the important parameter for the determination of water quality. The current existing method of measuring turbidity of water could come in bulky size or small portable turbidity meter. The ability to handle many samples and implementation of on-line monitoring is limited for such devices while some do not support this feature. Taking measurements would be laborious and time consuming especially when the sources of samples are located in remote places which are difficult to be accessed by human. In this research, an alternative turbidity measurement system called the “Optical Transmission-Based Water Turbidity Measurement System” is designed and its performance is analysed and compared to the measurement from a standard turbidity meter. The concept of the proposed measurement system is to make the turbidity measurement remote, easy to handle and more flexible. The use of fibre optic as the element of carrying light enables measurement taken at the source of sample but could be remotely controlled from other place by the user. The design for the fibre optic set-up, transmitter circuit, receiver circuit and signal conditioning circuit were covered. The assembly program for Peripheral Interface Controller (PIC) was also created.